2014
DOI: 10.1177/0037549714521305
|View full text |Cite
|
Sign up to set email alerts
|

Bond graph modeling for fault diagnosis: the continuous stirred tank reactor case study

Abstract: Supervision of chemical and biochemical processes is difficult due to various factors, for example the evolution of nonlinear state variables, uncertainties in parameters and disturbances, and system operating conditions. The complexities arise out of the energetic couplings in the model. In this work, the bond graph representation, as a unified and multidisciplinary tool, is used for dynamic modeling and diagnosis for process engineering, incorporating the chemical kinetics of an equilibrated reaction, heat a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In Ould‐Bouamama et al, the causal and structural properties of the BG model are used not only for system dynamics simulation but also to design FDI algorithms for online supervision of faults affecting sensors, actuators, and physicochemical components and phenomena. For details regarding BG‐based FDI, one is referred to the previous studies …”
Section: Problem Formulation and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ould‐Bouamama et al, the causal and structural properties of the BG model are used not only for system dynamics simulation but also to design FDI algorithms for online supervision of faults affecting sensors, actuators, and physicochemical components and phenomena. For details regarding BG‐based FDI, one is referred to the previous studies …”
Section: Problem Formulation and Related Workmentioning
confidence: 99%
“…For details regarding BG-based FDI, one is referred to the previous studies. [20][21][22] On the other hand, the PH formalism is especially of great importance regarding the modeling, control, and fault detection of systems due to many advantages, which explain why it is desired to preserve the particular structure. One of the strong aspects of the PH formalism is to expose the relations between the energy storage, dissipation, and interconnection structure; this framework underscores the physics of the system, and it ensures power conservative interconnections through the Dirac structures.…”
Section: Related Workmentioning
confidence: 99%
“…Several authors have shown an interesting in the application of this approach to modeling (see, for example, Sanchez and Medina, 23 Mezghani et al, 24 and Banerjee and Karmakar 25 for optimization, Badoud et al 26 for fault detection, and isolation and Borutzky 27 and El Harabi 28 for control of PV and wind energy systems 29 ).…”
Section: Bond Graph Modelingmentioning
confidence: 99%
“…In this present work, we are concerned to deal with AFTC systems in order to compensate failure effects. In addition to these analytical laws, we also find graphical ones which become more and more used in several engineering fields to diagnose [4] and to control [16] systems positing here some beneficial points for this use. Graphical approaches are often chosen for their physical signification and structural representation, their easy reading and interpretation using bonds and interconnections and exclusively because they emphasis cause-effect relations and power exchange through bonds.…”
Section: Introductionmentioning
confidence: 98%